Clinical characteristics and microbiota of progressing slight chronic periodontitis in adults - Anne C. R. Tanner (Blackwell Synergy, 2007)
Aim: This study sought clinical and microbial risk indicators for progressing slight periodontitis. Material and Methods: One hundred and seventeen periodontally healthy or slight periodontitis adults (20–40 years) were monitored clinically at 6-month intervals followed by supragingival cleaning. Inter-proximal sites with 41.5mm increase in clinical attachment over 18 months were considered disease active. Subgingival plaque was analysed by 78 16S rDNA and 38 whole-genomic DNA probes and by PCR to Porphyromonas gingivalis and Tannerella forsythia. Characteristics were compared between active and inactive subjects. Results: Twenty-two subjects showed disease activity principally at molars. Mean baseline gingival and plaque indices, bleeding on probing, probing depth and clinical attachment level (CAL) were higher in active subjects. DNA probes detected species and not-yet-cultivated phylotypes from chronic periodontitis, although few species were associated with active subjects. By PCR P. gingivalis (p50.007) and T. forsythia (p50.075) were detected more frequently during monitoring in active subjects. Stepwise logistic analysis associated baseline levels of gingival index, clinical attachment and bleeding with subsequent clinical attachment loss. Conclusions: Gingivitis and CAL were significantly associated with progressing slight periodontitis in 20–40-year-old adults. Species associated with moderate and advanced chronic periodontitis were detected in slight periodontitis.